Efektivitas Distribusi Zakat pada Masa Umar bin Abdul Aziz dan Relevansinya terhadap Model Pengentasan Kemiskinan di Indonesia - Fadhlan, Muhammad; Darin Diffana Athifah; Wahdan Saidurroihan; Lina Marlina; Ana Fauziya Diyana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the effectiveness of zakat distribution during the leadership of Umar bin Abdul Aziz and its relevance to poverty alleviation models in Indonesia. Structural poverty remains a persistent challenge in Indonesia’s economic development, requiring systematic and sustainable solutions. Within Islamic economic thought, zakat functions not only as a religious obligation but also as a fiscal instrument capable of promoting social welfare and economic independence. This research employs a qualitative approach through historical and literature study methods, analyzing classical Islamic governance practices alongside contemporary zakat management in Indonesia. The findings reveal that the success of zakat distribution under Umar bin Abdul Aziz was supported by centralized governance, strong institutional reform of Baitul Mal, strict supervision, and integrity-based leadership, resulting in effective wealth redistribution and significant poverty reduction. The study further finds that productive zakat distribution, institutional integration, regulatory reinforcement, and digital transparency are crucial elements for enhancing the performance of zakat institutions in Indonesia. The implications suggest that strengthening governance, accountability, and productive empowerment programs can transform zakat into a strategic socio-economic policy instrument capable of addressing structural poverty in a sustainable manner.